Fractalkine/CX3CL1 modulates GABAA currents in human temporal lobe epilepsy. Issue 10 (13th September 2013) - Roseti, Cristina; Fucile, Sergio; Lauro, Clotilde; Martinello, Katiuscia; Bertollini, Cristina; Esposito, Vincenzo; Mascia, Addolorata; Catalano, Myriam; Aronica, Eleonora; Limatola, Cristina; Palma, Eleonora
Summary Purpose The chemokine fractalkine/CX3CL1 and its receptor CX3CR1 are widely expressed in the central nervous system (CNS). Recent evidence showed that CX3CL1 participates in inflammatory responses that are common features of CNS disorders, such as epilepsy. Mesial temporal lobe epilepsy (MTLE) is the prevalent form of focal epilepsy in adults, and hippocampal sclerosis (HS) represents the most common underlying pathologic abnormality, as demonstrated at autopsy and postresection studies. Relevant features of MTLE are a characteristic pattern of neuronal loss, as are astrogliosis and microglia activation. Several factors affect epileptogenesis in patients with MTLE, including a lack of γ‐aminobutyric acid (GABA)ergic inhibitory efficacy. Therefore, experiments were designed to investigate whether, in MTLE brain tissues, CX3CL1 may influence GABAA receptor (GABAAR) mediatedtransmission, with a particular focus on the action of CX3CL1 on the use‐dependent decrease (rundown) of the GABA‐evoked currents (IGABA), a feature underlying the reduction of GABAergic function in epileptic tissue. Methods Patch‐clamp recordings were obtained from cortical pyramidal neurons in slices from six MTLE patients after surgery. Alternatively, the cell membranes from epileptic brain tissues of 17 MTLE patients or from surgical samples and autopsies of nonepileptic patients were microtransplanted into Xenopus oocytes, and IGABA were recorded using the standard two‐microelectrode voltage‐clamp technique. Immunohistochemical staining and double‐labeling studies were carried out on the same brain tissues to analyze CX3CR1 expression. Key Findings In native pyramidal neurons from cortical slices of patients with MTLE, CX3CL1 reduced IGABA rundown and affected the recovery of IGABA amplitude from rundown. These same effects were confirmed in oocytes injected with cortical and hippocampal MTLE membranes, whereas CX3CL1 did not influence IGABA in oocytes injected with nonepileptic tissues. Consistent with a specific effect of CX3CL1 on tissues from patients with MTLE, CX3CR1 immunoreactivity was higher in MTLE sclerotic hippocampi than in control tissues, with a prominent expression in activated microglial cells. Significance These findings indicate a role for CX3CL1 in MTLE, supporting recent evidence on the relevance of brain inflammation in human epilepsies. Our data demonstrate that in MTLE tissues the reduced GABAergic function can be modulated by CX3CL1. The increased CX3CR1 expression in microglia and the modulation by CX3CL1 of GABAergic currents in human epileptic brain suggests new therapeutic approaches for drug‐resistant epilepsies based on the evidence that the propagation of seizures can be influenced by inflammatory processes.